Effects of dietary counseling on gestational weight gain and pregnancy outcomes in obese pregnant women prospective randomised controlled trial in Hospital Sultanah Bahiyah, Alor Setar, Kedah (Dec 2013-Dec 2014) - Hamid, Sharifa Azlin (2015)
Introduction: Obesity is a serious and increasing health problem in the Western World and also in Malaysia. Prevalence of obesity in Malaysia is 7.5% and estimated prevalence of obesity in women in Malaysia was 16.6%. The numbers keep increasing each year and it gives a significant impact to the reproductive age women. Obese women who get pregnant carried higher maternal morbidity and perinatal morbidity and mortality. Pregnancy complications such as Gestational Diabetes Mellitus(GDM), Pre-Eclampsia(PE), Caeserean Section, infections and thromboembolic disease significantly associated with obese mother. Observational studies indicate that the rate of pregnancy complications among obese pregnant women can be limited if weight gain during pregnancy is restricted. Heavier women may benefit from avoiding high and very high gestational weight gain (GWG), which brings only a slight increase in the risk of growth restriction for the infant.On recent data, especially in Asian population, there is no evidence-based prenatal counseling protocol available to prevent excessive gestational weight gain. Objective: To evaluate the effects of dietary counseling in obese pregnant women on gestational weight gain and pregnancy outcomes in Hospital Sultanah Bahiyah, Alor Setar, Kedah Patients and Methods: This was a prospective randomized controlled trial, commenced on the 1st December 2013 and ended on the 30th December 2014. It was carried out in Hospital Sultanah Bahiyah, Alor Setar, Kedah.There were 120 patients with obesity Class I,II and III recruited in this study, equally randomised into two groups; obese patients in intervention group with dietary counseling and control group with routine prenatal care group.The intervention group received dietary counseling from the only one dedicated nutritionist for at least once in each trimester of pregnancy. The main dietary counseling remains on diet and caloric restriction. The main outcome measured was the mean difference of gestational weight gain between two groups. Secondary outcomes included maternal outcome such as incidence of Gestational Diabetes Mellitus,Pregnancy Induced Hypertension,Pre Eclampsia, mode of delivery, Post Partum Haemorrhage; and fetal outcomes included mean gestational age, mean birth weight, shoulder dystocia and Apgar Score. Results: A total of 120 women were randomized into two groups of 60, the dietary counseling and routine prenatal care groups. Baseline demographic characteristics were similar between the study groups. The dietary counseling group gained significantly less gestational weight gain than did the routine prenatal care group 7.6 kg (SD 1.54) compared with 9.1kg (SD 1.86), p<0.001 with 95% CI: 0.83-2.07. In a multiple logistic regression, statistically significant variables in the maternal outcome include gestational age, GDM and spontaneous labour. Fetal outcome with significant variables include Apgar score in 1 minute, 5 minutes, 10 minutes and diagnosis of pneumonia Conclusions: The study shows dietary counseling in obese pregnant women has significant benefit in reducing gestational weight gain and improving pregnancy outcomes in maternal side such as prolonged gestational age of delivery, reducing occurrence of GDM and higher proportion goes into spontaneous labour. Fetal outcomes also significantly improved in term of Apgar Score and reducing number of fetus develop pneumonia.